Health Education About Toilet Training On Maternal Behavior In The Application of Toilet Training In Preschool Children - Utami, Rahayu Budi; Nurhayati, Risa; Putri, Ayu Sandra Saskia (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Preschoolers must toilet training independently. In fact, there are still many preschool children cant do. Knowing the effect of health education on toilet training on maternal behavior in implementing toilet training in preschool children. Pre experimental method. The study was conducted on March 4-9 2020. The population 80 respondents, a sample of 36 respondents. The independent variable for health education about toilet training, the dependence on the mother's behavior in implementing toilet training. Data collection using a questionnaire. Wilcoxon analysis test with α = 0.05. Of the 36 respondents, most of the mothers' behavior before the intervention 27 respondents (75%) behaved moderately, after the intervention almost all 28 (80.6%) behaved well, obtained ρ-value 0.000 ≤ α, so there is an effect of health education on maternal behavior in application of toilet training in preschool children. In health education there is a learning process that can improve behavior.